A Dual Mesh Method for a Non-Local Thermistor Problem - Abderrahmane El Hachimi; Moulay Rchid Sidi Ammi; Delfim F.M. Torres (Symmetry, Integrability and Geometry: Methods and Applications, 2006)
We use a dual mesh numerical method to study a non-local parabolic problem arising from the well-known thermistor problem.